181 Levosulpiride for Premature Ejaculation: A Systematic Review and Meta-Analysis. (1st May 2022) - Arshad, A.; Irfan, M.; Inam, M.; Hussain, N.H.N.; Ismail, S.B.
ABSTRACT: Introduction: PE is diagnosed in the men that have from the first intercourse persistently occurring ejaculation in ≤1 minute of intercourse (lifelong PE) or significantly reduced ejaculation time (≤3 minutes) later in life (acquired PE), failed to delay ejaculation almost all the time of sexual intercourse, and have developed negative personal and mental conditions (e.g., bother, frustration, distress) and eventually sexual avoidance. Upon stimulation, the glans penis relays sensory information to ejaculatory centers (medial preoptic area, paraventricular nucleus, and periaqueductal grey) in the brain, which integrate the peripheral events of the seminal emission, ejaculation, and orgasm. The nucleus paragigantocellularis then modulates the efferent output of dopamine (DA) that inhibits the release of serotonin and ultimately cause ejaculation through D2 receptors. D2 receptor agonists decrease latency time and ejaculatory threshold and increase the frequency of ejaculation in rats. Furthermore, the damage to dopaminergic neurons increased the latency time of ejaculation. Selective serotonin reuptake inhibitors could be an effective treatment of PE, but they impose adverse side effects. Another approach to PE treatment is the inhibition of DA and/or D2 receptors. Levosulpiride (N-[[(2S)-1-ethylpyrrolidin-2-yl]methyl] 2-methoxy-5-sulfamoylbenzamide) is an antagonist of D2 receptors on the dopaminergic neurons of the central and peripheral nervous system. It has shown therapeutic effects primarily in psychiatric (depression, vertigo and schizophrenia) and motor disorders of the upper gastrointestinal tract (gastroesophageal reflux disease, irritable bowel syndrome, dyspepsia and emesis), but also PE. Some previous studies have reported improvements in intravaginal ejaculation latency time (IELT) in men with PE when they were treated with levosulpiride. However, a few studies have reported no significant improvement after levosulpiride treatment. Objectives: This review aims to report the efficacy of levosulpiride in the treatment of PE and improvement of IELT. Methods: The present study is a systematic review and meta-analysis. PubMed, Science Direct, and Google Scholar were searched for this review. Randomized control trials (RCTs) comparing levosulpiride with a placebo or other medicine were selected. Results: A total of 97 articles were retrieved from the database search, of which only 4 RCTs containing 203 men met the selection criteria. All 4 RCTs were included in the systematic review while only 2 were included in the meta-analysis. A high selection and detection bias was found in both of these studies. The meta-analysis also showed the odds of improving IELT in PE patients using levosulpiride to be significantly higher (p < 0.05) compared to those who used a placebo (OR: 100.81, 95% confidence interval (CI) [13.12-774.90], I 2 = 0%). The odds of improving IELT for > 5 min (500% improvement) were also significantly higher (p < 0.05) compared to the placebo groups (OR: 38.88, 95% CI [5.12-295.29], I 2 = 0%). Furthermore, the odds of improving IELT for > 1 min but < 5 min were also significantly higher (p < 0.05) than the placebo groups (OR: 32.84, 95% CI [4.15-259.75], I 2 = 0%). Conclusion: Levosulpiride improved IELT, but even so, limited studies are available on this topic. Additional research is thus required to support the present review's findings. Disclosure: Work supported by industry: no.